Student perceptions of small and large group discussions as active learning strategies in undergraduate medical education: a cross-sectional study from Gwalior (M.P) - Lilhore, Shiwani; Verma, Tinku; Chouksey, Mahendra (International Journal of Research in Medical Sciences, 2026)
Background: Competency-based medical education focuses on the active learning interventions that improve communication, critical thinking, and the engagement of the learner. In undergraduate medical education, SGD and LGD are common interactive methods of teaching; even so, little evidence has been found about the perceptions of students regarding their efficacy in the framework of Indian CBME. To assess students’ perceptions regarding the content, delivery, and effectiveness of SGD and LGD, to evaluate their perceived impact on communication and analytical skills, and to identify areas for improvement. Methods: The study was a cross-sectional feedback study carried out among undergraduate MBBS students (Batch 2021) in the Department of Community Medicine in a tertiary care medical college in Gajra Raja Medical College Gwalior (M.P). A pre-established, pre-tested feedback questionnaire will be administered after SGD and LGD sessions that will take place in July 2024. The descriptive statistics was used to analyze data of 162 complete responses and reported in terms of frequencies and percentages. Results: Most of the respondents felt that the group meetings were suitable, informative, and interesting. The majority of students indicated that they had developed better skills in walking into groups, relating with peers, building relationships, and critical thinking. Conclusion: Small and large group discussions were considered as good active learning competencies that increased cognitive and interpersonal abilities of undergraduate medical students.